Filsafat Konstruktivisme dan Implikasinya terhadap Pendidikan Islam Berorientasi Peserta Didik - Ahmad Rizki Suwardi; Ahmad Zhafari Musyafa; Ailia Fadias Putriamansyah (CV Omah Kreator, 2025)
Constructivist philosophy posits that knowledge is not transferred passively but is actively constructed by learners through experience, reflection, and interaction. In the context of Islamic education, this paradigm aligns with the concept of tarbiyah, which places learners as active subjects with innate potential (fitrah) to grow. This study aims to examine the relevance of constructivism within the philosophy of Islamic education and its implications for student-centered learning. A literature review method was employed by analyzing modern constructivist theories alongside the perspectives of Islamic education scholars such as Al-Ghazali, Ibn Sina, and Abuddin Nata. The findings indicate that constructivism can be integrated into Islamic education through the strengthening of teachers’ roles as murabbi and learning facilitators, the implementation of dialogical, participatory, and reflective methods, and the development of learning environments that promote meaningful experiences. Furthermore, this approach supports the development of character, independence, and critical reasoning in learners, as emphasized in the Qur'an, particularly in Surah Al-Alaq (1–5) and Surah Luqman (12–19). The study concludes that constructivism does not contradict Islamic values; rather, it can enrich Islamic education practices in the 21st century when implemented contextually and grounded in the principles of tauhid.